Navigating complexity: a case report of concurrent central cord syndrome and stroke in an elderly gentleman - Kee, Hoe Teong; Harun, Mohd Hezery; Mohamed Ramlee, Fadzrul Abbas; Lim, Teck Siang; Che-Hamzah, Fahrudin (Springer Science and Business Media LLC, 2024)
Central cord syndrome (CCS) predominantly manifests in elderly individuals with pre-existing cervical spondylosis resulting from hyperextension mechanisms. However, it is not exclusive to the older population and can occur in younger individuals following traumatic cervical spine injuries or, less frequently, due to nontraumatic causes. The impact of this syndrome is more pronounced in the upper extremities, where motor function experiences greater impairment compared to sensory function. CCS presents itself along a spectrum of severity. At one end, individuals may exhibit weakness confined to the hands and forearms while preserving sensory function. At the other extreme, complete quadriparesis may occur, albeit with sacral sparing being the sole indication of an incomplete spinal cord injury. This spectrum underscores the varied and nuanced clinical presentations within CCS. Moreover, concurrent acute stroke presentations can mimic CCS symptoms, further complicating the diagnostic process. The challenge lies in differentiating these two distinct conditions, particularly in an elderly population with overlapping risk factors. This diagnostic challenge adds a layer of complexity to clinical decision-making and underscores the importance of comprehensive evaluations in patients presenting with neurological symptoms. This case report presents a 73-year-old gentleman with a history of a recent stroke and motor vehicle accidents, highlighting the diagnostic challenges and multidisciplinary management required for concurrent CCS and stroke mimicry. This report is unique, as there are no existing case report publications detailing concurrent CCS and stroke. It emphasizes the necessity for a comprehensive diagnostic approach and coordinated care in managing such intricate cases.